Peran Komitmen Organisasi dalam Memediasi Motivasi, Lingkungan Kerja, Kesejahteraan, dan Kepemimpinan Partisipatif terhadap Kinerja - Arnomo, Ilham (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2017)
The purpose of this research is to analyze the effect of direct and indirect motivation, work environment, well-being and participatory leadership on performance. Research conducted at the Airlangga University Library, data analysis techniques using path analysis. The number of respondents as many as 72 people. The results showed that there were four hypotheses are rejected, namely direct influence of work environment on performance, indirect influence of work environment on performance through direct influence on organizational commitment and leadership participatory on performance and influence indirectly the participatory leadership on performance through organizational commitment The findings in this research suggests that the influence of work environment and participatory leadership still hasn't been able to encourage the staff of the library to committed to the Organization, so that library staff are still not able to contribute optimal performance.